2015
DOI: 10.1542/peds.2014-3299
|View full text |Cite
|
Sign up to set email alerts
|

Prescription Opioid Epidemic and Infant Outcomes

Abstract: BACKGROUND AND OBJECTIVES: Although opioid pain relievers are commonly prescribed in pregnancy, their association with neonatal outcomes is poorly described. Our objectives were to identify neonatal complications associated with antenatal opioid pain reliever exposure and to establish predictors of neonatal abstinence syndrome (NAS). METHODS:We used prescription and administrative data linked to vital statistics for mothers and infants enrolled in the Tennessee Medicaid program between 2009 and 2011. A random … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
202
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 272 publications
(209 citation statements)
references
References 33 publications
6
202
1
Order By: Relevance
“…However, this body of literature demonstrates tremendous variability; infants treated with morphine may be treated as long as 37 days or as short as 12 days. 9,[23][24][25] This variation supports the theory that the environment of care is likely more important than the medication used for treatment. Two recent multicenter Ohio collaborative reports and a single-center study in NICUs showed a decreased LOS to between 18 and 23 days with use of a standardized weaning protocol.…”
Section: Figuresupporting
confidence: 59%
See 2 more Smart Citations
“…However, this body of literature demonstrates tremendous variability; infants treated with morphine may be treated as long as 37 days or as short as 12 days. 9,[23][24][25] This variation supports the theory that the environment of care is likely more important than the medication used for treatment. Two recent multicenter Ohio collaborative reports and a single-center study in NICUs showed a decreased LOS to between 18 and 23 days with use of a standardized weaning protocol.…”
Section: Figuresupporting
confidence: 59%
“…The physician group delayed initiating pharmacotherapy in the first 24 to 36 hours when exposure to long-acting opioids together with tobacco or selective serotonin reuptake inhibitors exacerbated early withdrawal symptoms; these exposures co-occur frequently. 23 …”
Section: Planning the Interventionmentioning
confidence: 99%
See 1 more Smart Citation
“…11 This problem persists, as evidenced by a recent study that showed among 112 029 pregnant women, 31 354 (28.0%) were prescribed at least 1 opioid pain reliever during pregnancy. 12 It is estimated that 1 in 5 children grows up in a home in which someone uses drugs or misuses alcohol. 7 The exact number of children living with adults with SUDs is unknown 13 ; however, an estimated 8.3 million children younger than 18 years (12%) were residing with at least 1 substance-dependent or substance-using parent between 2002 and 2007.…”
Section: Epidemiology Of Substance Use In the United Statesmentioning
confidence: 99%
“…1 Although concern regarding substance use in pregnancy is not new, it has recently increased among health care providers, the public, and policy makers as the opioid epidemic's impact reached an increasing portion of the US population, including pregnant women and their infants. 2,3 Several recent studies highlighted an increase in prescription opioid use among women of childbearing age 4 and among pregnant women. 5,6 As opioid use among pregnant women increased, the rate of infants in the United States experiencing opioid withdrawal after birth, known as neonatal abstinence syndrome (NAS), grew nearly fivefold over the past decade.…”
Section: Introductionmentioning
confidence: 99%